Preliminary study of interactivity between mercury and cells labeled with carboxymethyl chitosan coated quantum dots - He, Zhenyu (Ecotoxicology (London, England), 2014)
This paper describes the development of a simplified and rapid method for the aqueous synthesis of quantum dots (QDs) with CdTe cores and gradient CdS external shells (CdTe/CdS QDs) aided by microwave irradiation. In order to improve the biocompatibility of the CdTe/CdS QDs, these QDs were then interacted with carboxymethyl chitosan (CMC) so as they could be used as fluorescent probes in the aqueous phase. As fluorescent probes, these modified QDs were successfully used for imaging live Madin-Darby canine kidney (MDCK) cells. Then mercury was incubated with the micro-system formed by quantum dots labeled MDCK. Fluorescence quenching was occurred in the micro-system after 24 h. The micro-system's fluorescence quenching caused by mercury(II) was consistent with the fluorescence quenching equation and displayed a good linearity between the quenched fluorescence intensity of mercury(II). The preliminary results indicated that this micro-system can be used for detection of trace amounts of mercury in vivo and interaction process investigation between mercury and cells